Visual evaluation as a quality control program in Dental Radiology - Damian, Melissa Feres (2008)
Purpose: The objective of this study was to evaluate whether changes of density and contrast in dental radiographs caused by degradation of processing solutions can be visually identified. Methods: Sixty periapical radiographs were taken using a density scale and a phantom, and were processed in a portable dark room using processing solutions in progressive degradation over 30 days of the study. The films of the density scale were used to evaluate the percentage of density and contrast decrease, and the exposed films with the phantom were used for visual evaluation. Eighteen dentists scored the radiographs according to the possibility of image interpretation. Results: Only radiographs with 45% average loss of density and 62% of contrast were considered inappropriate for diagnostic purposes. Conclusion: It was concluded that the visual clinical evaluation is inadequate to be used as a single program of quality control in Dental Radiology. Key words: Dental radiography; quality control; diagnostic; processing